ECT‐related anxiety during maintenance ECT: A prospective study. (19th September 2022) - Obbels, Jasmien; Gijsbregts, Els; Verwijk, Esmée; Verspecht, Shauni; Lambrichts, Simon; Vansteelandt, Kristof; Sienaert, Pascal
Abstract: Objective: Despite the established safety of electroconvulsive therapy (ECT), ECT‐related anxiety (ERA) remains one of the most distressing complications of ECT. ERA is reported to diminish during an acute course of ECT, but it was never studied during maintenance ECT (M‐ECT). Our aim was to study the trajectories of ERA during M‐ECT and how they differ from trajectories during the acute course. Methods: Thirty‐nine patients with unipolar or bipolar depression, retained for M‐ECT after an acute ECT course, were included. ERA was assessed the morning before each ECT session using the ECT‐related Anxiety Questionnaire (ERAQ). Results: ERA remained stable during M‐ECT (RC = −0.05 (SE = 0.06), t (8.35) = −0.86, p  = 0.42), while ERA declined significantly during the acute course (RC = −0.85 (SE = 0.30), t (33.6) = −2.81, p  = 0.0082). During the acute course, patients with a psychotic depression were more anxious at baseline ( t (32)= −2.42, p  = 0.02), and showed a significant decline in ERAQ scores (RC = −1.65 (SE = 0.46), t (31.6) = −3.56, p  = 0.0012), whereas patients with a non‐psychotic depression were less anxious at baseline and retained stable ERAQ scores during the acute course (RC = −0.06 (SE = 0.41), t (32.1) = −0.14, p  = 0.89). Whereas a correlation ( r  = 0.48) was noticed between the decline of depression severity and ERA during the acute course, this was not the case during M‐ECT. Conclusion: ERA runs a stable course during M‐ECT, after having decreased during the acute course. During the acute course, ERA trajectories differed significantly between patients with a psychotic and non‐psychotic depression. Decline of depression severity and ERA are significantly connected during the acute course of ECT. Both depression severity and ERA remain stable during M‐ECT.